Implications of Vaginal Instrumental Delivery for Children's School Achievement: A Population-based Linked Administrative Data Study. Issue 3 (September 2020) - Hsieh, D.C.; Smithers, L.G.; Black, M.; Lynch, J.W.; Dekker, G.; Wilkinson, C.; Stark, M.J.; Mol, B.W.
Abstract : ( Aust N Z J Obstet Gynaecol . 2019;59:677–683) Instrumental vaginal delivery is a relatively common obstetric procedure in both Australia and the UK, accounting for ∼10% to 13% of deliveries. It is typically performed in cases of prolonged second stage of labor, fetal compromise, or limited ability of the mother to push. While instrumental deliveries are performed when obstetricians believe the benefits outweigh the risks, there are numerous potential side effects for both mother and fetus. These include maternal soft tissue tears and anal and urinary sphincter dysfunction as well as fetal trauma injuries, such as intracranial and subgaleal bleeding, lacerations, and cranial nerve injuries. Researchers have been concerned about the potential long-term neurodevelopmental effects of instrumental vaginal delivery, but previous studies have not adequately compared the development of children who were born via spontaneous vaginal delivery versus those born via instrumental vaginal delivery. This study was conducted to determine whether vacuum extraction, forceps, or normal vaginal deliveries had an effect on academic performance at 8 years of age.